Where there is no government : enforcing property rights in common law Africa - Joireman, Sandra Fullerton (New York ; Oxford : Oxford University Press, 2011)
In sub-Saharan Africa, property rights law is an especially potent source of instability. This book is at once an authoritative and powerful account of the central dilemma in Africa, and a prescription for addressing it.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Land tenure -- Law and legislation -- Africa, English-speaking.; Land tenure -- Law and legislation -- Ghana; Land tenure -- Law and legislation -- Kenya; Land tenure -- Law and legislation -- Uganda